Empathy for Pain from Adolescence through Adulthood: An Event-Related Brain Potential Study - Mella, Nathalie; Studer, Joseph; Gilet, Anne-Laure; Labouvie-Vief, Gisela (Frontiers in Psychology, 2012)
Affective and cognitive empathy are traditionally differentiated, the affective component being concerned with resonating with another’s emotional state, whereas the cognitive component reflects regulation of the resulting distress and understanding of another’s mental states (see Decety and Jackson, 2004 for a review). Adolescence is a critical period for the development of cognitive control processes necessary to regulate affective processes: it is only in young adulthood that these control processes achieve maturity (Steinberg, 2005). Thus, one should expect adolescents to show greater automatic empathy than young adults. The present study aimed at exploring the neural correlates of affective (automatic) and cognitive empathy for pain from adolescence to young adulthood. With this aim, Event Related Potentials (ERPs) were recorded in 32 participants (aged 11 to 39) in a task designed to dissociate these components. ERPs results showed an early automatic frontocentral response to pain (that was not modulated by task demand) and a late parietal response to painful stimuli modulated by attention to pain cues. Adolescents exhibited earlier automatic responses to painful situations than young adults did and showed greater activity in the late cognitive component even when viewing neutral stimuli. Results are discussed in the context of the development of regulatory abilities during adolescence.